Quick Access to Forestry Information through CD-ROM - Subramonian, C. (Indian Forester, 1998)
The paper describes the content. subject coverage of databases available on CD-ROM and impact of CD-ROM technology as an information retrieval tool of forestry information centres. The forestry information retrieval study helps to save the valuable time of the researchers and foresters. Ultimately this study reveals the immense use of CAB International's CD-ROM product TREE-CD.